A Comparative Evaluation of the Role of Cone Beam Computed Tomography (CBCT) Imaging and Orthopantomography (OPG) in Sinus Augmentation Procedures: An Original Study - S.Girish Rao; Sushma Mehta; Abhishek Singh Nayyar (Journal of Dentistry And Oral Implants, 2016)
Context: The present study was undertaken to do a comparative evaluation of the role of Cone Beam Computed Tomography (CBCT) imaging and Orthopantomography (OPG) for pre-operative implant planning in combination with sinus grafting procedures in order to assess sinus anatomy and morphology and the existing bone height in three dimensions. Aims: To assess sinus anatomy and morphology and the existing bone height in three dimensions. Materials and Methods: Pre-operative assessment of maxillary sinuses for implant planning using CBCT imaging was performed on 20 sinuses (17 patients). These patients were subjected to orthopantomographs and CBCT imaging both pre-operatively and post-operatively. CBCT imaging helped to decide the type of sinus augmentation procedure best suited for the patients as per the individual needs and depending on the residual alveolar bone height, timing of implant placement, sinus morphology, anticipation of complication and comparative analysis between pre-and post-procedural gain in vertical alveolar bone height and increase in bone density. Statistical Analysis: The results were tabulated and statistically analyzed using Paired and Unpaired t-tests. Results: In the majority of cases, there was a concordance between the treatment type based on pre-operative and post-operative CBCT scans. The assessment of sinus morphology revealed a significantly higher detection rate of abberations in the form of sinus mucosal hypertrophy and septae on CBCT which were imperceptible on routine radiographs. The most appealing result was that vertical alveolar bone height could be measured precisely and there was a significant increase in surgical confidence and a significantly better prediction of complications when using CBCT imaging. Conclusions: A pre-operative planning based on CBCT imaging seems to improve sinus diagnostics and helps to execute a better treatment plan. Also, it is a good tool for the comparison of vertical alveolar bone height pre-and post-operatively following sinus augmentation procedures using various graft materials.
Keywords: CBCT